CRIMINAL RESPONSIBILITY IN THE CRIMES COMMITTED BY ORGANIZED STRUCTURES OF POWER: jurisprudence analysis in the light of International Criminal Law - Dutra, Bruna Martins Amorim (Revista da Faculdade de Direito da UERJ - RFD, 2012)
DOI: http://dx.doi.org/10.12957/10.12957/rfd.2012.1930